Peningkatan Return On Investment terhadap Harga Saham di PT Gudang Garam Tbk Tahun 2013-2018 - Budi Lesmana; Diki Sodikin (LPPM POLITEKNIK LP3I BANDUNG, 2020)
This study aims to determine the effect of return on invesment on stock prices at PT Gudang Garam Tbk Period 2013-2018. Every company is trying to get a big profit and investors want their investment to continue to increase, investment will increase with the right stock investment, one of the indicators is that stock prices tend to be stable or always increase. The research metod used i this research is Descriptive Analysis and Verifikatif. Descriptiive to answer questions and verification to answer the relationship in the formulation of the problem. Data collection techniques using the study of literature and documentation. Data Analysis using Simple Linear Analysis, Determination Coefficient Analysis and Hypothesis Testing through partial t test. The result of study can be concluded that the significance value for Return On Invesment with Stock Price is 0,010 > 0,5. Thus the hypothesis is accepted meaning that ROI affects the stock price. Teh amount of adjusted R2 value is 0,841 which means that the variability of the dependent variable that can be explained by the variability of the independent variable is 84,1% while the remaining 15,9% is explained by other variables not included in the regression model.